A Developmental Embodied Choice Perspective Explains the Development of Numerical Choices - Michirev, Alexej; Musculus, Lisa; Raab, Markus (Frontiers in Psychology, 2021)
The goal of the special issue is to explore how an embodied view can redirect our understanding of decision-making. To achieve this goal, we contribute a developmental embodied choice perspective. Our perspective integrates embodiment and bounded rationality from a developmental view in which the body provides cues that are used in abstract choices. Hereby, the cues evolve with the body that is not static and changes through development. To demonstrate the body’s involvement in abstract choices, we will consider choices in numerical settings in which the body is not necessarily needed for solution. For this, we consider magnitude judgement task in which one chooses the larger of two quantities. In a nutshell, our perspective will pinpoint how the concept of embodied choices can explain the development of numerical choices.